Lessons from the European spaghetti bowl - Richard Baldwin (Asian Development Bank Institute (ADBI), 2013)
European economic integration fascinates and inspires for the way it brought peace to a continent torn by violent and long-standing rivalries. The lessons from Europe, however, cannot be applied directly as the degree of the European Union's supranationality is unthinkable elsewhere. This paper discusses how Europe overcame the specific problem of overlapping free trade agreements (FTAs) with the Pan-European Cumulation System which instituted common rules of origin, regional cumulation of value, and completed the full matrix of bilateral FTAs. After this, Europe had what can be thought of as a "customs union" for rules of origin.
Keywords: F15; F2; 330; european economic integration; european union; eu; europe; trade; free trade agreements; fta; regional integration; rules of origin; Freihandelszone; Eurozone; Herkunftsbezeichnung; EU-Recht; EU-Staaten